Consideration of underlying causes of pneumothoraces in patients presenting with their first pneumothorax. (November 2017) - Jackson, Emma; Nichani, Raj
We report a case of cardiac arrest secondary to pneumothorax. The patient failed to improve, and further investigation showed an underlying condition predisposing the patient to the development of pneumothoraces – lymphangioleiomyomatosis. This highlights the importance of follow-up and investigation in patients presenting with their first pneumothorax.